A Study of Philippine Hospital Management Administrative Systems - Fred Avestruz (Philippine Institute for Development Studies (PIDS), 1995)
Hospitals are very important institutions for the economic and social well being of society. However, its success relies heavily on its managerial capacity. Hence, this paper aims to contribute to the hospital's managerial success through a better understanding of hospital management and their roles in society.
Keywords: 330; health care; health facilities; hospitals; health centers